1998
DOI: 10.1086/305615
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Structure in Cold Dark Matter Universes

Abstract: We present an analysis of the clustering evolution of dark matter in four cold dark matter (CDM) cosmologies. We use a suite of high resolution, 17-million particle, N-body simulations which sample volumes large enough to give clustering statistics with unprecedented accuracy. We investigate a flat model with Ω 0 = 0.3, an open model also with Ω 0 = 0.3, and two models with Ω = 1, one with the standard CDM power spectrum and the other with the same power spectrum as the Ω 0 = 0.3 models. In all cases, the ampl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
519
2
4

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 506 publications
(558 citation statements)
references
References 105 publications
(121 reference statements)
33
519
2
4
Order By: Relevance
“…By the mid-1990s, many cosmological simulation studies included both open-CDM models and Λ-CDM models, along with Ω m = 1 models incorporating tilted inflationary spectra, nonstandard radiation components, or massive neutrino components (e.g., Ostriker and Cen 1996;Cole et al 1997;Gross et al 1998;Jenkins et al 1998). Once normalized to the observed level of CMB anisotropies, the large-scale structure predictions of open and flat-Λ models differed at the tens-of-percent level, with flat models generally yielding a more natural fit to the observations (e.g., Cole et al 1997).…”
Section: Historymentioning
confidence: 99%
“…By the mid-1990s, many cosmological simulation studies included both open-CDM models and Λ-CDM models, along with Ω m = 1 models incorporating tilted inflationary spectra, nonstandard radiation components, or massive neutrino components (e.g., Ostriker and Cen 1996;Cole et al 1997;Gross et al 1998;Jenkins et al 1998). Once normalized to the observed level of CMB anisotropies, the large-scale structure predictions of open and flat-Λ models differed at the tens-of-percent level, with flat models generally yielding a more natural fit to the observations (e.g., Cole et al 1997).…”
Section: Historymentioning
confidence: 99%
“…High-resolution cosmological simulations over the past decade have shown that on small scales (P1-2 Mpc) the correlation function of matter strongly deviates from the power-law shape. The direct implication of this result is that the spatial distribution of galaxies on small scales is biased with respect to the overall distribution of matter in a nontrivial scale-dependent way (e.g., Klypin et al 1996;Jenkins et al 1998). In view of this, it is very interesting to understand whether the power-law shape of the correlation function is a fortuitous coincidence or a consequence of some fundamental physical process.…”
Section: Introductionmentioning
confidence: 99%
“…The formation and evolution of clusters depends sensitively on cosmological parameters like the mean matter density in the universe Ω m (Thomas et al 1998;Jenkins et al 1998;Beisbart et al 2001). Therefore it is important to determine the dynamical state of clusters at different redshifts, i.e.…”
Section: Introductionmentioning
confidence: 99%